Statistical analysis of recent rule revision effects for tactical and strategic elements in curling - Kondo, Y.; Yanagi, H.; Ptaszynski, M.; Aihara, S.; Masui, F. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
In this paper, PCA is performed on a set of tactical elements calculated by scoring opportunity analysis for the men`s and women`s Japanese Championships 2017, 2022, and 2023 with different rules. Curling is a winter sport called "chess on ice". Curling is considered as a system system consisting of multiple elements, which can be divided into three categories: physical, human and tactical. Among these, strategic and tactical factors are considered to be the most important in top-level competition. In addition, in the curling world, some rules are sometimes changed in order to improve players` skills and tactics. In this study, we analyzed the changes in tactical factors due to the rule changes. As a result, it is considered that the nautical zone rule is not effective in men`s competitions. In the women`s competitions, scoring points by stealing became more important each time the rules were changed.